Überlegungen zum Stellenwert des jüdischen Kleinkredits im Reichsgebiet bis zur Mitte des 14. Jahrhunderts - Müller, Jörg (Aschkenas, 2025)
The awarding of the Nobel Peace Prize to economist Muhammad Yunus in 2006 in recognition of his work on microcredit theory and its implementation has also given further impetus to historical research on small loans. While Jewish small loans in the fifteenth-century Holy Roman Empire, which are comparatively well documented, have already been the subject of some research, there is still a lack of relevant studies for the period before the Black Death pogroms. This is primarily because small-scale loans were rarely recorded in writing, and much of the relevant documentation has been destroyed. However, an evaluation of the few surviving written records suggests that small loans and microloans already dominated lending by Jewish moneylenders in the German Kingdom in the thirteenth and first half of the fourteenth centuries.